2021
DOI: 10.1186/s12859-021-04410-2
|View full text |Cite
|
Sign up to set email alerts
|

Concatenation of paired-end reads improves taxonomic classification of amplicons for profiling microbial communities

Abstract: Background Taxonomic classification of genetic markers for microbiome analysis is affected by the numerous choices made from sample preparation to bioinformatics analysis. Paired-end read merging is routinely used to capture the entire amplicon sequence when the read ends overlap. However, the exclusion of unmerged reads from further analysis can result in underestimating the diversity in the sequenced microbial community and is influenced by bioinformatic processes such as read trimming and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Notably, the method M-DJ inferred a highest number of taxa as compared to the other two approaches (Figure 3). Thus, in accordance with the earlier finding (Dacey and Chain, 2021), this study also supports that the analysis of merged sequences along with the directly-joined unmerged reads could improve the resolution of microbial composition in the samples. Further, the most important taxa (top ten) that could be used to explain the ecosystems were found to be different (Figure 4) for M, DJ and M-DJ, which could be due to the differences in the ASV distribution and abundance of taxa observed in the respective groups.…”
Section: Inference Of Microbial Community Composition and Dominant Mi...supporting
confidence: 92%
See 1 more Smart Citation
“…Notably, the method M-DJ inferred a highest number of taxa as compared to the other two approaches (Figure 3). Thus, in accordance with the earlier finding (Dacey and Chain, 2021), this study also supports that the analysis of merged sequences along with the directly-joined unmerged reads could improve the resolution of microbial composition in the samples. Further, the most important taxa (top ten) that could be used to explain the ecosystems were found to be different (Figure 4) for M, DJ and M-DJ, which could be due to the differences in the ASV distribution and abundance of taxa observed in the respective groups.…”
Section: Inference Of Microbial Community Composition and Dominant Mi...supporting
confidence: 92%
“…A recent study using mock community data has highlighted that directly-joined reads that lack overlapping regions along with the merged sequences could improve the taxonomic classification (Dacey and Chain, 2021). This study investigates how the analysis of merged sequences along with directly-joined unmerged PE reads ameliorates the problems associated with low quality data in environmental microbiome research.…”
Section: Introductionmentioning
confidence: 99%
“…Using the DADA2 pipeline, the sequence reads were truncated at 120 bp on the basis of -the quality of sequence data and the reverse reads were reverse-complemented and concatenated with the forward reads. There is a possibility of reducing microbiome diversity estimates through exclusion of sequence reads that fail to merge (Aigle et al 2019;Dacey and Chain 2021). Concatenating paired reads together without a sequence overlap has been identified as an alternative to overcome this problem (Aigle et al 2019;Dacey and Chain 2021).…”
Section: Microbiome Analysis By High-throughput 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…There is a possibility of reducing microbiome diversity estimates through exclusion of sequence reads that fail to merge (Aigle et al 2019;Dacey and Chain 2021). Concatenating paired reads together without a sequence overlap has been identified as an alternative to overcome this problem (Aigle et al 2019;Dacey and Chain 2021).…”
Section: Microbiome Analysis By High-throughput 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…Towards this, we performed two independent runs and the generated reads were further analysed using DADA2 pipeline [14]. It has also been shown that the choice of reference database impacts the downstream analysis significantly [15]. In this study we used SILVA database as reference for taxonomic assignment.…”
Section: Introductionmentioning
confidence: 99%